Effect of 1-D and 2-D carbon-based nano-reinforcements on the dry sliding-wear behaviour of 3Y-TZP ceramics. Issue 6 (June 2021) - Rodríguez-Rojas, Fernando; Cano-Crespo, Rafael; Borrero-López, Oscar; Domínguez-Rodríguez, Arturo; Ortiz, Angel L.
Abstract: The dry sliding-wear behaviour of a zirconia doped with 3 mol% yttria (3Y-TZP) monolithic and of two 3Y-TZP composites, these latter with the same ultrafine-grained microstructure as the former but reinforced with either 1-D carbon nanofibres (CNFs) or 2-D reduced graphene oxide (rGO) nanoplatelets, was evaluated by ball-on-disk tests at moderate load, and compared critically. It was found that 3Y-TZP, 3Y-TZP/CNFs, and 3Y-TZP/rGO undergo mild wear, in the three cases by abrasion with contributions from both plastic deformation and fracture (with varying severities depending on the sample). It was also found that wear resistance does not correlate with hardness or toughness, but with whether or not there is formation of self-lubricating tribofilms on the contact surface. Specifically, once pulled-out, 2-D rGO nano-reinforcements impose solid-state lubrication that reduces the coefficient of friction (CoF), thus providing 3Y-TZP/rGO with superior wear resistance relative to both 3Y-TZP and 3Y-TZP/CNFs. 1-D CNF nano-reinforcements, however, do not form such tribofilms, or hardly do so, thus having no effect on the CoF and wear resistance. Implications are discussed of both the dimensionality of the carbon-based nano-reinforcements and the testing conditions for the microstructural design of ceramic composites for tribological applications.